PENGARUH KUALITAS LAYANAN TERHADAP TINGKAT KEPUASAN DAN WORD OF MOUTH PELANGGAN MICE DI RAMADA BINTANG BALI RESORT - Wadhi, Yohanes Paulus Hanny; Wardana, Made; Suprapti, Ni Wayan Sri (E-Jurnal Ekonomi dan Bisnis Universitas Udayana; VOLUME.06.NO.06.TAHUN 2017, 2017)
This study is aimed at determining the effect of service quality on satisfaction and word of mouth of mice costumers in Ramada Bintang Bali Resort. The method of sampling is done by puposive sampling, with the total of respondents of 150. Data are collected through questioners and data analysis techniques using Structural Equation Model (SEM) with application software analysis moment of structure (AMOS) . The results show that (1) Quality of service has positive and significant effects on costumers’ satisfaction, (2) Satisfaction effects positively and significantly on word of mouth, and (3) The quality of service has the same effects on word of mouth.
Keywords: Service Quality, Costumers Satisfaction, Word Of Mouth